2008
DOI: 10.1111/j.1752-699x.2008.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational tuberculosis following extremely short exposure

Abstract: By adding modern molecular epidemiological methods to traditional epidemiological surveys, a more detailed picture of MT-transmission pathways can be obtained, showing that MT transmission can occur even after extremely short exposure. This stresses the necessity for adequate respiratory protection among hospital staff taking care of patients with pulmonary symptoms suspected for TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
1
2
1
Order By: Relevance
“…As for the extrapulmonary tuberculosis in our study; lymph node involvement (19.2%) is the most common presentatin followed by the pleura (8.3%) and bone (4%). Previous studies reported the extrapulmonary tuberculosis rate in different populations [13,[17][18][19][20]. Compared with them, extrapulmonary tuberculosis rate was higher in our study population.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…As for the extrapulmonary tuberculosis in our study; lymph node involvement (19.2%) is the most common presentatin followed by the pleura (8.3%) and bone (4%). Previous studies reported the extrapulmonary tuberculosis rate in different populations [13,[17][18][19][20]. Compared with them, extrapulmonary tuberculosis rate was higher in our study population.…”
Section: Discussioncontrasting
confidence: 52%
“…Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Although tuberculosis primarily involves the lungs, any sort of extrapulmonary involvements can be seen [8][9][10][11][12][13]. Recording, analysis, and reporting the tuberculosis cases is the mainstay of the tuberculosis control program according to the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Only sporadic information was available on the duration of exposure for the cases in our study. However, one of the confirmed cases of occupational TB transmission was seen after extremely short exposure; this case has previously been reported by Kamper-Jørgensen et al [ 20 ]. This underscores the additional role genotyping has in contact tracing as conventional methods for this case would most likely have pointed on other more obvious potential links in which duration of exposure was longer.…”
Section: Discussionsupporting
confidence: 55%
“…In the meantime, K amper- J ørgensen et al . [ 20 ] reported M. tuberculosis transmission from a patient to a nurse following an extremely short exposure by retrospective evaluation of the Danish TB Subtyping Database, comprising >6000 DNA patterns from TB patients nationwide. N odieva et al .…”
Section: Discussionmentioning
confidence: 99%